2012
DOI: 10.1136/annrheumdis-2011-154146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of previously undiagnosed rheumatic diseases in pregnancy

Abstract: In our population approximately 2.5% and 1% of first trimester pregnant women had a previously undiagnosed UCTD and definite systemic rheumatic disease, respectively. These conditions were associated with significant negative effects on the outcome of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…More effort should be put into public health education to increase the public's awareness of SLE and health care providers should consider the possibility of SLE when young female patients are presented with disorders involving multiple organs. Moreover, it is critical to identify pre-SLE patients as early as possible, for example, through the use of questionnaire [35] and screening tools such as the ANA test. Timely treatment for those at elevated risks of developing SLE might help to reduce the high mortality associated with SLE [36].…”
Section: Discussionmentioning
confidence: 99%
“…More effort should be put into public health education to increase the public's awareness of SLE and health care providers should consider the possibility of SLE when young female patients are presented with disorders involving multiple organs. Moreover, it is critical to identify pre-SLE patients as early as possible, for example, through the use of questionnaire [35] and screening tools such as the ANA test. Timely treatment for those at elevated risks of developing SLE might help to reduce the high mortality associated with SLE [36].…”
Section: Discussionmentioning
confidence: 99%
“…The enrolment criteria included: a) singleton pregnancy; b) antenatal care and delivery at our Department; c) fluency in the Italian language; d) no previous diagnosis or treatment of connective tissue diseases; e) absence of fetal malformations or chromosomal anomalies. The characteristics of the study and the validation of the methods used have already been reported elsewhere (8). Briefly, after informed consent was obtained and before the medical evaluation was conducted, each woman was asked to complete a screening questionnaire including any connective tissue disorder symptoms (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…[10] Results from the present study suggest the potential utility of a similar approach in PAH patients. Analogously to the effort made in the field of interstitial lung disease with the recent introduction of the concept of interstitial pneumonia with autoimmune features [32] we propose that a population of PAH patients show autoimmune features which may rely undetected at a first examination and which require a multidisciplinary expertise and the mandatory performance of ANA testing and capillaroscopy.…”
Section: Discussionmentioning
confidence: 63%
“…[10] International guidelines for PH diagnosis and management [11] recommend identifying associated CTD and recently several new diagnostic/classification criteria have been proposed for many CTDs. [1214] .…”
Section: Introductionmentioning
confidence: 99%